Supportive supervision to enhance students' academic achievement in the situation of COVID-19 Prachuap Khiri Khan Primary Educational Service Area District Office 2 - Choangchan, Araya (Journal for Developing the Social and Community, 2023)
The objectives of this research were: 1. to assess the competence in supportive supervision to enhance students' learning achievement in the situation of COVID-19; COVID-19 Situation 3. Assess the knowledge and understanding of learning management to enhance students' learning achievement in the situation of COVID-19 4. Assess the satisfaction of administrators and teachers with supportive supervision to raise the level. Student's Academic Achievement in the COVID-19 Situation 5. Assess the students' and parents' satisfaction towards raising the student's academic achievement in the situation of COVID-19 6. Evaluate the learning outcomes of students before and after raising the level of student achievement in the situation of COVID-19In this research is an experimental research. Type of quasi-experimental experiment (Pre Experimental Design), which the researcher conducted the experiment according to the research model, One Group Pretest Posttest Design. sample group In this research, 1) 7 administrators 2) 12 teachers in 7 schools in 1 branch of Tanaosri group. Using volunteer sampling, 3) 328 students and 4) 328 parents. The research instruments consisted of 1) a test to measure learning achievement in Thai language and mathematics Grade 3 2) Student satisfaction questionnaire on learning management to enhance learning achievement at the national level 3) Thai and mathematical skills assessment form 4) Satisfaction questionnaire about Supervision to enhance learning achievement 5) Teaching supervision manual 6) Teacher performance assessment form 7) Interview form 8) Supervising Teaching Skills Assessment 9) Teaching Supervisory Knowledge Test 10) Satisfaction Questionnaire About Enhancement of Learning Achievement The qualitative data was analyzed by content analysis, quantitative data analysis, statistical analysis by using descriptive statistic, i.e. percentage value; The mean, mean percentage and standard deviation were analyzed.The results showed that The supervising teachers had the ability to provide supportive supervision to enhance learning achievement after the experiment higher than before the experiment. Teachers receiving supervision had higher capacity in learning management to enhance learning achievement after the experiment than before the experiment. At the .05 level, the school administrators, teachers, students and parents were satisfied with the supportive supervision to raise their learning achievement.